Writing difficulties of the English composition II students of the Foreign Language Department of the University of El Salvador influencing the quality of writing on their expected products to improve their writing skill, semester I-2018. - Andrade Reyes, Bartolomé Remberto; López Rosales, Roxana Guadalupe; Vásquez Contreras, Jorge Omar (2024)
This study covers a research within the area of writing difficulties in the EFL Classroom. This research project aims to give a look at writing professors’ attitudes and reactions towards working with writing difficulties when teaching Composition. The data for this study was collected through the mixed methods (qualitative and quantitative method.) Therefore, face to face interviews and a written questionnaire were applied to get the data. The informants who participated in this study were students of the subject, English Composition II, from groups 1, 2, 3 and 4 and professors of the previous groups from the Foreign Language Department at the University of El Salvador, semester-1 2018. The surveys (interviews) were conducted during the informants’ lessons and also in the professors´ offices. The study presents that the professors feel that it is challenging to work with students who have writing difficulties, since those students might be unmotivated, lacking of misspelling problems, deficiencies in grammar, vocabulary, punctuation, when using cohesive devices and capitalization. However, the informants believe that teachers need to motivate their students to write more, use peer assessment, give feedback to the students that might have difficulties at the moment of writing a paragraph or an essay in order to achieve development, good essays, academic papers or good grades. Moreover, the study shows that professors do not use any specific method when working with writing; instead each professor tries to see what his/her students have difficulties with, and subsequently he will look for solutions based specifically on every student’s needs. That is why at the end of this study some recommendations are given in order to improve the writing difficulties Composition II students, semester I-2018 presented.